USE OF HANDCUFFS IN THE JURY TRIAL COURTROOM EXCEPTIONALITY, WRITTEN JUSTIFICATION, AND EFFECTS ON THE VERDICT (CIPEEX, 2025)
This paper examines the use of handcuffs in Brazilian jury trials in light of Binding Precedent No. 11 of the Federal Supreme Court and Decree-Law No. 3,689/1941 (Code of Criminal Procedure), identifying when restraint is lawful, how it must be justified, and whether it may bias jurors. It aims to delineate the exceptional nature of handcuffing, the requirement of written reasons and record, and the procedural consequences of non-compliance (nullity and potential liability), while assessing impacts on human dignity and the presumption of innocence. Methodologically, it adopts a doctrinal-normative, bibliographic approach with an inductive method focused on documentary analysis of the CPP and the STF’s binding precedent. The findings indicate that handcuffs are permissible only in cases of resistance, well-founded risk of escape, or danger to the physical integrity of the defendant or others, and the measure must be expressly reasoned and recorded; displaying a handcuffed defendant before the jury may stigmatize and improperly influence fact-finding, so judges should prevent undue contamination and order removal when appropriate. It concludes that handcuffing is exceptional and contingent on written justification; disregard of the legal parameters entails nullity and possible liabilities, whereas judicial caution preserves the defendant’s dignity, the presumption of innocence, and the integrity of the verdict.
Keywords: binding precedent no. 11; handcuffs; jury court; Human dignity